Efektivitas perawatan metode kanguru terhadap stabilitas frekuensi denyut jantung pada bayi berat lahir rendah - Kristina Yuliani; Heni Puji Wahyuningsih; Hesty Widyasih (Poltekkes Kemenkes Yogyakarta, 2013)
The cause of infant Mortality Rale (IMR) in Indonesia was due to LBW 29% because of less nice handling. Monitor health status require LBW for early detection of health problems, there are with measurements of vital signs especially heart rate frequency on LBW responsible to maintain cardiac-output, which otherwise adequate will result in the-exchange of insufficiency of oxygen, nutrients and rest of the metabolism of the body less efficient, disruption of physiological functions on the body. KMC keep the heart rate frequency stability. Objective: To determine the effectiveness KMC to the heart rate frequency stability of LBW. Methods: Observational Analytic study with one group pretest posttest design with time series. Retrieval with purpose of sampling by the number of respondents 40 LBW done KMC. The kind of data on this research is the primary with an instrument data of research decision of the oximeter. Data of analysis using standard significance Paired Sample T-test with test 0.05. Results; From the result obtained that before KMC frequency heartbeat unstable 1O% and after 100% stable. The average frequency of heart rate prior to KMC was 126,81 times a minute, after KMC is 140,71 times a minute and the difference is 13,89. Analysis of the results obtained p-value 0,00 (<0,05) so the obtained results that increase heart rate frequency after the KMC is done. Conclusion: KMC effective in the stability of the frequency heart rate of LBW.